Analisis Getaran Primary Air Fan (PAF) Sebagai Dasar Maintenance Pada Sistem Boiler CFB MB 26 PT Indah Kiat Pulp and Paper Tbk Perawang - Armin Jon Tua Manalu; Abdul Gafur (Jurnal INOVATOR, 2026)
Primary Air Fan (PAF) is an important rotating equipment in the Circulating Fluidized Bed (CFB) boiler system that supplies primary air to support the fluidization and combustion processes. The reliability of the PAF significantly affects combustion stability and steam production continuity. This study aims to analyze the vibration characteristics of Primary Air Fan units as a basis for predictive maintenance implementation in the Boiler CFB MB 26 system at PT Indah Kiat Pulp and Paper Tbk Perawang. Vibration measurements were conducted using an SKF QuickCollect Sensor, while bearing temperatures were measured using an infrared thermal gun. The collected data were analyzed using the Root Mean Square (RMS) method and evaluated according to ISO 10816-3 standards. The results showed that PAF A had a maximum vibration value of 0.5 mm/s and was classified in Zone A (Good Condition), while PAF B reached 1.7 mm/s and was classified in Zone B (Acceptable Condition) with an indication of slight unbalance. Bearing temperatures ranged from 31.1°C to 42.4°C and remained within normal operating limits. The results indicate that vibration analysis is effective for machine condition monitoring and supports predictive maintenance implementation